The potential of South African timber products to reduce the environmental impact of buildings - Crafford, Philip L.; Blumentritt, Melanie; Wessels, C. Brand (South African Journal of Science, 2017)
South Africa was the first country in Africa to implement a locally developed green building rating tool and has a growing number of rated green building projects. The method of life-cycle assessment can help to compare and assess the environmental performance of building products. At present, more than 70% of all sawn timber in South Africa is used in buildings, mainly in roof structures. Light gauge steel trusses have recently also been gaining market share. However, to date, no studies have been conducted that quantify and compare the environmental impacts of the different roof truss systems in South Africa. We thus compared several roof truss systems (South African pine, Biligom and light gauge steel) found in low- and medium-income house designs in South Africa using a simplified life-cycle assessment approach. Our results show that the two timber systems had overall the lowest environmental impact. Although the difference between the timber systems was small, light gauge steel had a 40% higher normalised impact over all assessed environmental impact categories. The benefit of biogenic carbon dioxide present in timber proved to play a significant positive role in the global warming potential impact and could even be further reduced if wood were used to generate energy at its end-of-life. This study demonstrates the potential advantage of using local timber products to reduce the environmental impact of the truss and building industry in South Africa. Significance: Timber truss systems showed overall lower environmental impact than light gauge steel trusses, with implications for green building.